2017
DOI: 10.1016/j.chembiol.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Targeting Small-Molecule Inhibitors of the Staphylococcus aureus FMN Riboswitch Disrupt Riboflavin Homeostasis in an Infectious Setting

Abstract: Riboswitches are bacterial-specific, broadly conserved, non-coding RNA structural elements that control gene expression of numerous metabolic pathways and transport functions essential for cell growth. As such, riboswitch inhibitors represent a new class of potential antibacterial agents. Recently, we identified ribocil-C, a highly selective inhibitor of the flavin mononucleotide (FMN) riboswitch that controls expression of de novo riboflavin (RF, vitamin B2) biosynthesis in Escherichia coli. Here, we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 49 publications
(82 reference statements)
0
70
0
3
Order By: Relevance
“…Riboswitches are ideal targets because analogues of small‐molecule metabolites can be used to disrupt normal riboswitch regulation of the gene expression. Riboswitch inhibitors have been found . While inhibitors of metabolic riboswitches are promising sites for the design of new antibiotics, they are still prone to induce bacterial resistance because the drug binds to a single target molecule that could readily be mutated to decrease drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Riboswitches are ideal targets because analogues of small‐molecule metabolites can be used to disrupt normal riboswitch regulation of the gene expression. Riboswitch inhibitors have been found . While inhibitors of metabolic riboswitches are promising sites for the design of new antibiotics, they are still prone to induce bacterial resistance because the drug binds to a single target molecule that could readily be mutated to decrease drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[179] Confirmation that bacterial riboswitches can indeed be selectively targeted was obtained from the identification of two novel inhibitors of the FMN riboswitch in 2015:5FDQD and ribocil-C (Figure 13 b). [183] Although targeting riboswitches is avery promising approach which increases the number of new antibacterial targets,g ood in vivo inhibition without rapid development of resistance remain ac hallenge for future investigation. [180] Ribocil-C is a" drug-like" small molecule that is chemically unrelated to FMN.I tw as first identified by comparative phenotypic screening of as ynthetic smallmolecule library.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…If the respective metabolite is essential for life, this will lead to a growth stop and/or death of the bacterial cell. Several studies have demonstrated that riboswitches are indeed druggable [68,16,4749]. The most prominent investigation employed a phenotypic screen and identified ribocil that acts as a structurally distinct mimic of the natural ligand flavin mononucleotide to repress ribB gene expression and inhibit cell growth [7].…”
Section: Discussionmentioning
confidence: 99%
“…This makes the structure-based design of modified ligand analogs and ligand mimics rather challenging. Nevertheless, the identification of novel potent ligands is a topic of intense research because ever since their discovery, riboswitches have been viewed as promising targets for the development of novel antibiotic strategies [16]. Likewise, efforts to engineer riboswitches for imaging purposes [1719] or as biotechnological tools for the detection of endogenous and non-endogenous small molecules are in the focus of synthetic biologists interested in understanding and reprogramming cellular behavior [20].…”
Section: Introductionmentioning
confidence: 99%